INOVASI PELAYANAN AKTA GRATIS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG DI RUMAH SAKIT UMUM UNGARAN - Rizkiani, Oktrianita; S., Endang Larasati (Journal of Public Policy and Management Review, 2018)
A local government, who is organizing a public service, are required to improve the quality of rapidity, simplicity, and efficiency. By the implementation of free certificate service in Ungaran Hospital, it expected to fulfill those demands and increase public awareness to arrange the administration. The objectives of this research are to know the implementation of free certificate’s innovation service and to know the obstacle’s factors of implementation in Ungaran Hospital. This research is a descriptive qualitative research that used interview, observation, and documentation method as collecting the data. The innovation’s attributes are needed in this research. By using three indicators, they are benefit gained, people’s conformity to the needs, and facility of service provided, the result shows that the implementation of the innovation service runs pretty well. The obstacles of doing innovation service are: it is hard to people to understand what are the procedures of service and the hospital’s employees cannot make their own decision, they need to wait for the boss’s decision. For the recommendations, it would be better if the hospital does the evaluation of certificate’s innovation service, adding the guidelines like a banner in the waiting room and the hospital’s corridors, and the last increase the number of employee in the delivery room.